Towards of the question of the Ethnography of the childhood of the Gypsy population of Bessarabia of the XIX Century - Svetlana PROCOP (Revista de Etnologie şi Culturologie, 2019)
In the middle of the XIX century in Russia, an explosion of interest in the peoples inhabiting the Russian Empire was noted. During this period, a large number of scientific-historical and ethnographic reviews were published, which described various stories from the life of the so-called small nations, including Roma. Among the peoples of the Russian Empire in the XIX century, Gypsies living in Bessarabia were of particular interest. The article is based on published materials, ethnographic reports and essays of the XIX century about the gypsies of Bessarabia and Romania, whose authors are M. Kogalnichanu, A. Zashchuk, K. Hanatsky. An attempt is made to analyze the descriptions that contain characteristics related to Roma children. Particular attention is paid to the general and special in these judgments. We consider it appropriate in this context to accompany these characteristics with illustrative material, since we are talking about the XIX century, when photography was still in its infancy. This refers to the first etchings of the XVII century, which depicts a camp of gypsies who appeared in Europe in the XV century, as well as drawings from XIX century art publications depicting gypsy children.